Mach–Zehnder Modulators for Microwave Polarization Measurement in Astronomy Applications - Francisco J. Casas; Guillermo Pascual-Cisneros (Sensors, 2023)
This paper presents a study of the performances of different Mach–Zehnder modulation technologies with applications in microwave polarimeters based on a near-infrared (NIR) frequency up-conversion stage, allowing for optical correlation and signal detection at a wavelength of 1550 nm. Commercial Mach–Zehnder modulators (MZMs) are traditionally implemented using LiNbO3 technology, which does not enable integration for the fabrication of MZMs. In this work, we propose the use of an alternative technology based on InP, which allows for integration in the fabrication process. In this way, it is possible to obtain advantages in terms of bandwidth, cost, and size reductions, which yield results that are very interesting for wide-band applications such as microwave instrumentation for the study of the cosmic microwave background (CMB). Here, we describe and compare the modulation performances of different MZMs, with one commercial unit presenting a higher bandwidth than those in previous works, and another three InP integrated units provided by the Fraunhofer Institute for Telecommunications, Heinrich-Hertz-Institute (HHI). Then, these modulators were coupled to a microwave polarimeter demonstrator, which has also been presented previously, to compare the polarization measurement performances of each of the MZMs.